USING REMOTE REAL EXPERIMENTS IN HIGHER EDUCATION - LUKÁČOVÁ, Danka; BÁNESZ, Gabriel (Trends in education, 2017)
Experiments in the educational process are for illustration of new knowledge or phenomena. For the implementation of school laboratory experiments is however necessary technical equipment with technical parameters, which depend on the orientation and objectives of the experiment. This fact determines also its price. This problem can be partially solved using remote real experiments (RRE). Despite this, RRE are in teaching at universities applied in a very small extent. The authors answer the question why university teachers use (not use) RRE in teaching, what are the conditions for successful exploitation of RRE in the universities and what benefits in terms of professional didactics, respectively. Engineering and science bring RRE in their application to teaching. The authors also deal with the technical implementation of RRE, which is often very uneconomical in terms of their creators. To resolve this negative aspect of RRE is proposed to use logic controllers (LC). For proper use of RRE in teaching the author suggests to focus on the educational requirements that define what RRE should comply so as to be useful in teaching practice.
Keywords: Real remote experiment; university; questionnaire.